PROVIDING INFORMATION ACCESSIBILITY OF REHABILITATION PROGRAMS IN MEDICAL INSTITUTIONS OF THE RIVNE REGION - Vasyliv, V. B.; Beztelesna, L. I.; Tykhonchuk, L. Kh. (Rehabilitation and Recreation, 2025)
Purpose. The study aims to evaluate the information accessibility of websites of medical institutions in the Rivne region that provide rehabilitation services under packages No. 53 and No. 54 of the National Health Service of Ukraine (NHSU), in accordance with the Web Content Accessibility Guidelines (WCAG) 2.1. The objective was to identify accessibility barriers, analyze the level of compliance with international standards, and develop recommendations for improvement to enhance patients’ access to information about rehabilitation programs and increase the efficiency of the healthcare system. Materials. The study focused on 23 medical institutions in the Rivne region with active NHSU contracts for rehabilitation packages as of the first quarter of 2025. The assessment of information accessibility was conducted using a developed framework comprising six criteria: online presence, content completeness, compliance with WCAG 2.1 standards, usability, availability of contact information, and readability. Automated tools (WAVE, Accessibility Insights) and manual evaluation were employed for analysis. The study considered Ukrainian legislative requirements, particularly DSTU EN 301 549:2022, as well as international best practices in web accessibility. Results. It was found that 26% of medical institutions lack their own websites, creating a significant barrier to accessing information about rehabilitation services. Among existing websites, issues were identified with navigation, incomplete content, and non-compliance with WCAG 2.1 standards. The most common shortcomings include low text contrast (only 11.8% of sites meet requirements), lack of alternative text for images (47% of sites), and complex site structures. Usability and mobile adaptability also vary significantly: 78% of websites lack a search function, and the speed index ranges from 2.7 to 14.8 seconds. A positive aspect is the use of plain language on most sites, which enhances content comprehensibility. Conclusions. The study highlights the critical need to improve the information accessibility of medical institutions’ websites. Recommendations include creating websites for institutions without them, ensuring compliance with WCAG 2.1, simplifying navigation, expanding information about rehabilitation programs, and providing alternative communication channels. The proposed evaluation framework can serve as a universal tool for systematic analysis of information accessibility. Implementing these recommendations will promote transparency, enhance access to rehabilitation services for vulnerable populations, and improve the quality of healthcare in the region.